Find the derivative of the function y=(3+e^x+8x^3)^2*(2x+e^2x)

Asked on by for3cast

1 Answer | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

We have to find the derivative of y=(3+e^x+8x^3)^2*(2x+e^2x)

We can use the product rule here


y' = [(3+e^x+8x^3)^2*(2x+e^2x)]'

=>y' = [(3+e^x+8x^3)^2]*(2x+e^2x)]' + [(3+e^x+8x^3)^2]' *(2x+e^2x)]

=> y' = [(3+e^x+8x^3)^2]*(2+2e^2x) + [2*(3+e^x+8x^3)* (e^x+24x^2] *(2x+e^2x)

We get the derivative as: [(3+e^x+8x^3)^2]*(2+2e^2x) + [2*(3+e^x+8x^3)* (e^x+24x^2] *(2x+e^2x)

We’ve answered 319,846 questions. We can answer yours, too.

Ask a question